2018
DOI: 10.1080/09589236.2018.1523053
|View full text |Cite
|
Sign up to set email alerts
|

‘Atheism is not the problem. The problem is being a woman’. Atheist women and reasonable feminism

Abstract: While the percentage of religiously unaffiliated women is growing in the West, little is known about the relationship between atheism and feminism. This article redresses the gap by exploring women's identification with atheism and feminism. The central argument draws on qualitative interview data from the UK, Australia, the US, and Poland and emphasizes the role of atheism as a background identity marker through which female subjectivity is enacted in everyday life. The findings are twofold: first, atheism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…One can explain this gender imbalance by the fact that the women were stronger, and even militant, in their statements because Catholicism as a gender-traditional religion essentializes differences between men and women and promotes submission of the latter (Trzebiatowska 2019). Also, the presented results confirm what social surveys show: young women in Poland are generally more progressive than young men (see Pacewicz 2019).…”
Section: Against Hypocrisy and Conformismsupporting
confidence: 75%
“…One can explain this gender imbalance by the fact that the women were stronger, and even militant, in their statements because Catholicism as a gender-traditional religion essentializes differences between men and women and promotes submission of the latter (Trzebiatowska 2019). Also, the presented results confirm what social surveys show: young women in Poland are generally more progressive than young men (see Pacewicz 2019).…”
Section: Against Hypocrisy and Conformismsupporting
confidence: 75%
“…Anti-Atheist Discrimination and Atheist Identity Among Women. Like atheists in Smith's (2011) study of atheist identity formation and atheist women in Trzebiatowska's (2019) interviews, women in the present study found liberation in their atheism, in a general sense and with regard to gendered limitations of patriarchal, Christian hegemony.…”
Section: Atheism As a Concealable Stigmatized Identity Among Womensupporting
confidence: 46%
“…Indeed, Frost et al (2022) found women were more likely to conceal their atheism as compared to men. In a cross-national study of feminist, atheist women, participants described methods of making their atheism and feminism palatable to others, thus avoiding aggression and balancing femininity (Trzebiatowska, 2019).…”
Section: Anti-atheist Discriminationmentioning
confidence: 99%
“…Everything Dawkins considers anti-science and not conforming to the Truth is in his list of enemies. Both he and Dennett represent a new intellectual type and activ-3 There are many others who have analysed in detail the difficult relationship between the New Atheists and feminism (Beattie 2007;Brandt 2019;Stinson et al 2013;Trzebiatowska 2018) and those who analyse more generally the idea that Muslim women need saving by the West (Abu-Lughod 2013). 4 As Aaron Hughes notes, however, essentializing is not far from the commentators who emphasize that 'true Islam' is something other than the distorted militant hijacking of Islam that is practically 'synonymous with feminism, ecology, gender equality, LGBTQ2S rights, and the like' (Hughes 2021, 13).…”
Section: World Politics Human Rights and Islam's Perceived Problem Wi...mentioning
confidence: 99%